Well-posedness for density-dependent Boussinesq equations without dissipation terms in Besov spaces. (1st May 2017) - Qiu, Hua; Yao, Zheng'an
Abstract: In this paper, we consider the N -dimensional incompressible density-dependent Boussinesq equations without dissipation terms ( N ≥ 2 ) . We establish the local well-posedness for the incompressible Boussinesq system under the framework of the Besov spaces. In addition, we also obtain a Beale–Kato–Majda-type regularity criterion.